Study of micro-trichome (mict) reveals novel connections between transcriptional regulation of multicellular trichome development and specific metabolism in cucumber. (1st February 2021) - Pan, Jian; Zhang, Leyu; Chen, Guanqun; Wen, Haifan; Chen, Yue; Du, Hui; Zhao, Junlong; He, Huanle; Lian, Hongli; Chen, Huiming; Shi, Jianxin; Cai, Run; et al.
Abstract: Trichomes that cover the epidermis of aerial plant organs play multiple roles in plant protection. Compared with a unicellular trichome in model plants, the development mechanism of the multicellular trichome is largely unclear. Notably, variations in trichome development are often accompanied by defects in the biosynthesis of cuticle and secondary metabolites; however, major questions about the interactions between developmental differences in trichomes and defects in metabolic pathways remain unanswered. Here, we characterized the glabrous mutant mict / csgl1/cstbh via combined metabolomic and transcriptomic analyses to extend our limited knowledge regarding multicellular trichome development and metabolism in cucumber. Mict was found to be explicitly expressed within trichome cells. Transcriptomic analysis indicated that genes involved in flavonoid and cuticle metabolism are significantly downregulated in mict mutants. Further metabolomic analysis confirmed that flavonoids, lipids, and cuticle compositions are dramatically altered in mict mutants. Additional studies revealed that Mict regulates flavonoid, lipid, and cuticle biosynthesis by likely directly binding to downstream functional genes, such as CsTT4, CsFLS1, CsCER26, and CsMYB36 . These findings suggest that specific metabolic pathways (e.g., flavonoids and cuticle components) are co-regulated by Mict and provide insights into transcriptional regulation mechanisms of multicellular trichome development and its specific metabolism in cucumber.